Comparison of the denaturant-induced unfolding of the bovine and human alpha-lactalbumin molten globules. - Wijesinha-Bettoni, R; Dobson, C; Redfield, C (2001)
Residue-specific information on the urea-induced unfolding of the molten globule state of bovine alpha-lactalbumin (BLA) has been obtained using NMR spectroscopy. In agreement with previous studies on human alpha-lactalbumin (HLA) the unfolding process for BLA has been found to be non-cooperative. Both the alpha and beta-domains of the protein are substantially collapsed in the absence of denaturant but in both proteins the majority of the structure in the beta-domain unfolds prior to that in the alpha-domain. However, in BLA the protein unfolds completely in 10 M urea at 50 degrees C, whilst in HLA a stable core region persists even under these extreme conditions. Previous studies on HLA have identified eight residues that are crucial for the stability of the molten globule. Of these residues, only three are conserved in the sequence of BLA. By taking into consideration the differences in inter-residue contacts between the four alpha-helices arising from these substitutions, and the relative hydrophobicity of the helices in the two proteins, we show that it is possible to rationalise the observed differences in the behaviour of the molten globule states of the two proteins. Taken together, these results suggest that there may be a number of ways of stabilising a given protein fold, and the specific manner that this is achieved for a particular protein is determined by details of its sequence.